EFFECTIVENESS OF THE FILTRATION METHOD USING ACTIVATED CARBON FROM KEPOK BANANA PEELS AND ZEOLITE TO REDUCE KMnO4 LEVELS - Jumiati, Ety -; Husnah, Miftahul -; Asyari, Auly - (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2024)
The effectiveness of the filtration method using activated carbon from Kepok banana peels and natural materials such as zeolite has been studied. This research aims to reduce KMnO4 levels in well water so that it can be used for human needs. The well water samples used in the testing process with the filtration method were taken from a well located in Medan Marelan District, Tanah 600 Sub-district, North Sumatra Province. The utilization of Kepok banana peels for activated carbon to reduce KMnO4 levels involved using the chemical activator HCl 3M for 7 hours and an activation temperature of 600ºC for 45 minutes. The variations in composition used in the filtration method were sample A (75%:25%), sample B (50%:50%), and sample C (25%:75%). The most effective filtration result in reducing KMnO4 levels was sample A, with a KMnO4 reduction of 86.7%, which meets the clean water quality standards according to PERMENKES RI No 32 of 2017.